ANALISIS STRATEGI PEMASARAN TAHU SUMEDANG DENGAN MENGGUNAKAN METODE 4P GUNA MENINGKATKAN PENJUALAN DI UD. TAHU SUMEDANG 5 BERSAUDARA - Riswan Afandi; Siti Rahmah Sibuea; Wirda Novarika AK (Universitas Islam Sumatera Utara, 2023)
Marketing is an important activity of a company that produces products to sell with the aim of making a profit. One form of marketing strategy that has an important role in determining the level of product sales is the use of the marketing mix or also known as the 4P method (product, price, promotion, and place). This study aims to determine the increase in sales of sumedang tofu through a marketing strategy using the 4P method as well as factors (variables) that have a dominant influence in increasing sales of sumedang tofu at UD. Tahu Sumedang Dk 16. The research data was collected using a questionnaire given to 96 customers as the research sample, then data processing, analysis and evaluation were carried out so that it was concluded that sales of sumedang tofu were increased at UD. Tahu Sumedang Dk 16 is significantly influenced by the marketing strategy using the 4P method including product, price, promotion and place either simultaneously or partially with a positive direction. The influence of the 4P marketing strategy simultaneously on the increase in tofu sales is 71.4% or the remaining 28.6% is explained by variables other than those proposed in this study. The variable that has the most dominant influence in increasing sales of sumedang tofu is the price variable, which is 34.1%.